Influence Fashion Involvement and Shopping Lifestyle to Impulse Buying Moderation Positive Emotion and Positive Online Review Generation Z Users Uniqlo Products - Rifki Hafas, Hafriz; Murwani Muhar, Ani; Suvero Suyar, Annisha; Hayati, Azura (Journal of International Conference Proceedings, 2025)
The purpose of this study is to ascertain how fashion engagement and purchasing habits affect Generation Z's moderated favorable emotions for UNIQLO products. Moderated Regression Analysis (MRA) and multiple linear regression analysis approaches are used in this study design. 118 respondents who are Generation Z Uniqlo product customers make up the demographic and sample for this study, which employs associative research with a quantitative methodology. 1) Fashion participation and shopping lifestyle have a favorable and substantial influence on impulsive buying (sig value 0.05), according to the study's findings. 2) The association between fashion engagement and impulsive purchase behavior is moderated by positive mood. 3) The association between fashion participation and shopping lifestyle and impulsive purchases is not moderated by positive internet evaluations.